2017
DOI: 10.1016/j.jid.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentation Traits, Sun Exposure, and Risk of Incident Vitiligo in Women

Abstract: Vitiligo is the most common cutaneous depigmentation disorder worldwide, yet little is known about specific risk factors for disease development. Using data from the Nurses' Health Study, a prospective cohort study of 51,337 white women, we examined the associations between (i) pigmentary traits and (ii) reactions to sun exposure and risk of incident vitiligo. Nurses' Health Study participants responded to a question about clinician-diagnosed vitiligo and year of diagnosis (2001 or before, 2002-2005, 2006-2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…Vitiligo patients have decreased risk of developing skin cancer, especially melanoma 86,87 . Although sunburn is a provoking factor for vitiligo, 88,89 repigmentation of vitiligo lesions is almost impossible without UV exposure (natural or using phototherapy booths, lamps or lasers) 90,91 . Vitiligo patients should be advised to regularly expose their lesional skin to the sun until vitiligo lesions become pink, after which a high‐SPF broad‐spectrum sunscreen is advised to prevent sunburn 90,91 …”
Section: Pigmentary Disordersmentioning
confidence: 99%
“…Vitiligo patients have decreased risk of developing skin cancer, especially melanoma 86,87 . Although sunburn is a provoking factor for vitiligo, 88,89 repigmentation of vitiligo lesions is almost impossible without UV exposure (natural or using phototherapy booths, lamps or lasers) 90,91 . Vitiligo patients should be advised to regularly expose their lesional skin to the sun until vitiligo lesions become pink, after which a high‐SPF broad‐spectrum sunscreen is advised to prevent sunburn 90,91 …”
Section: Pigmentary Disordersmentioning
confidence: 99%
“…In addition, the later PTU treatment suggested that reducing the accumulated damages within a tolerable range could prevent melanophore cell death. To test this, different doses of PTU were used to suppress melanin production; the results showed that the lower the melanin production rate, the fewer melanophores die in nicastrin mutants (Supplementary Figure S11), which intriguingly echoed the association of blue and green eyes and tanning ability with vitiligo prevalence in previous clinical observations (Dunlap et al, 2017;Jin et al, 2010;Jin et al, 2012).…”
Section: Resultsmentioning
confidence: 85%
“…Second, melanin synthesis is associated with vitiligo (Jin et al, 2010;Jin et al, 2012). Third, vitiligo correlates with tanning ability (Dunlap et al, 2017). Fourth, melanocyte toxic factors are Tyrosinase substrates (van den Boorn et al, 2011;Tokura et al, 2015).…”
Section: Tyrosinase Inhibitors Could Be a Preventive Anti-vitiligo Drugmentioning
confidence: 99%
“…Mechanical trauma, including repetitive rubbing or friction, causes chronic loss of epidermal melanocytes, triggering vitiligo 79,80 . In terms of sun exposure, extensive tanning and sunburn‐induced blisters were associated with a higher risk of vitiligo in a prospective cohort of Caucasian females 81 . Also, the use of permanent hair dyes may trigger vitiligo in susceptible individuals 77,82 …”
Section: Resultsmentioning
confidence: 99%